2020
DOI: 10.3389/fpls.2020.00677
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study of Coleoptile Length in Different Chinese Wheat Landraces

Abstract: From the perspective of wheat yield improvement, the coleoptile is vital for successful crop establishment, and long coleoptile lengths (CLs) are preferred in wheat-growing regions where deep planting is practiced. To determine the genetic basis of CL, we performed a genome-wide association study on a set of 707 Chinese wheat landraces using 18,594 single-nucleotide polymorphisms and 38,678 diversity array technology sequencing markers. We accordingly detected a total of 29 significant markers [−log 10 (P) > 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 69 publications
5
29
0
Order By: Relevance
“…This result agrees with previous studies on wheat, which demonstrated QTL for number of shoots per plant and coleoptile length on the same chromosomes as found in the present study [17,51]. In addition, in this study, we detected significant QTL for number of shoots from regrowth on chromosomes 4B, 6A and 7B, which were also mapped with QTL for coleoptile length in wheat [49,51].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result agrees with previous studies on wheat, which demonstrated QTL for number of shoots per plant and coleoptile length on the same chromosomes as found in the present study [17,51]. In addition, in this study, we detected significant QTL for number of shoots from regrowth on chromosomes 4B, 6A and 7B, which were also mapped with QTL for coleoptile length in wheat [49,51].…”
Section: Discussionsupporting
confidence: 93%
“…Among the chromosomes with associated QTL in this study, chromosomes 2A, 2B, 4B, and 6B were also reported to harbor QTL for coleoptile length in a different study using the same diversity panel [51]. Furthermore, QTL for coleoptile length were also found on chromosomes 2B, 5A, 6B and 7B in a different wheat panel [49]. Similarly, under growth chamber conditions, nine significant QTL associated with coleoptile length were found on seven chromosomes, including 2B and 4B [51], which were associated with shoot length in this study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Wheat landraces show high genetic diversity and extensive phenotypic variation, such as early maturity, high numbers of kernel per spikelet, and good adaption to local environmental conditions (He and Huang, 2001;Hao et al, 2008). Genetic analyses of Chinese wheat landraces have revealed the basis of agronomic traits, such as yield-related traits (spikelets number per spike, tillers number, and thousand-kernel weight), plant morphological traits (flag leaf length, flag leaf width, and plant height; Liu et al, 2017;Ma et al, 2020), stress resistance (pre-harvest sprouting, drought-related traits, and phosphorusdeficiency tolerance; Zhou et al, 2017;Lin et al, 2019Lin et al, , 2020a, and disease resistance (powdery mildew and stripe rust; Xiao et al, 2013;Long et al, 2019). Analysis of gene diversity and polymorphism information content revealed the high diversity of Chinese wheat landraces (Liu et al, 2017;Long et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 51 loci significantly associated with adult-plant resistance to stripe rust were discovered in wheat landrace through GWAS (Long et al, 2019). Recently, a major locus of coleoptile length on chromosome 6B was revealed by GWAS in 707 Chinese wheat landraces (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%